Some Weather and Climatic Factors of the Inter-Epizootic Period in the Central-Caucasian High Mountain Natural Focus of Plague - V. M. Dubyansky; E. V. Gerasimenko; E. S. Kotenev (Проблемы особо опасных инфекций, 2025)
The aim of the work was to determine the relationship between the existing weather and climatic conditions and the inter-epizootic period in the Central-Caucasian high mountain natural focus of plague. Objectives: a) to identify weather and climate indicators potentially associated with the activity of a natural plague focus – optimal and pessimal values of these indicators for recording plague epizootics; b) to determine whether there are differences in the number of pessimal factors for recording epizootics during epizootic and inter-epizootic periods. Materials and methods. Data on the epizootic activity of the Central-Caucasian high mountain natural plague focus from 1987 to 2021 were studied. Information on the minimum, maximum and average air temperatures by months, the amount of precipitation by months, the average humidity, the value of atmospheric pressure were analyzed: a total of 72 weather indicators (Shadzhatmaz weather station). Statistical processing was carried out using a nonparametric sequential statistical recognition procedure, Spearman correlation analysis, and the Mann–Wilcoxon–Whitney test. To calculate statistics, the Python library sсipy. stat was used. Results and discussion. During high epizootic activity, the values of weather indicators were mainly in favorable ranges. After 2008, the values of weather indicators shifted mainly to unfavorable ranges. Values of weather indicators that are non-informative also tended to be beyond the limits of tolerance. Climatic changes adversely affect the epizootic activity of the focus. At the same time, the ecosystem of the focus is gradually adapting to climate change. It can be expected that the epizootic activity of the focus will be recorded sporadically, given some improvement in the weather conditions.